2008
DOI: 10.1179/146532808x375468
|View full text |Cite
|
Sign up to set email alerts
|

Hookworm causing melaena and severe anaemia in early infancy

Abstract: Hookworm infestation is usually acquired by transcutaneous penetration of larvae whilst walking barefoot on contaminated soil. We present a small infant who presented with melaena and severe anaemia requiring multiple blood transfusions where the cause of gastro-intestinal bleeding was found to be massive hookworm infestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Infantile hookworm disease is a distinct clinical entity which has only uncommonly been reported particularly from China, Nigeria, Nepal and aboriginal communities of Australia (2)(3)(4)(5)(6). There are a few reports of hookworm infestations in infants from India; two of these reports are among infants coming from Nepal (3)(4)(5)7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infantile hookworm disease is a distinct clinical entity which has only uncommonly been reported particularly from China, Nigeria, Nepal and aboriginal communities of Australia (2)(3)(4)(5)(6). There are a few reports of hookworm infestations in infants from India; two of these reports are among infants coming from Nepal (3)(4)(5)7).…”
Section: Discussionmentioning
confidence: 99%
“…It usually occurs in children when they begin to crawl or walk barefoot and come in contact with contaminated soil. Infants are rarely exposed to this infection; description is available from a few case reports only (2)(3)(4)(5)(6). Two cases of hookworm infection in infants who presented with massive gastrointestinal bleeding are presented.…”
mentioning
confidence: 99%
“…However, the consumption of a balanced diet through dietary diversification may be considered as an appropriate prevention and control strategy [59]. Several reports also revealed that worm load among rural children was highly prevalent [60]. …”
Section: Discussionmentioning
confidence: 99%
“…The incidence is much higher in children with around 2 million children under the age on examination there was only 40 grams weight gain over next 3 weeks. Baby was evaluated with septic screen which was negative (CRP-0.8mg/dl, leucocyte count 8,600/mm 3) Electrolytes (Na 138, K 4.2meq/l), Urine examination, Renal Function Test (Urea 28mg/dl, creatinine 0.6mg/dl), 2D Echo all were normal. Systemic examination was normal.…”
Section: Introductionmentioning
confidence: 99%
“…It may be explained by their frequent contact with the soil that is contaminated with the eggs. However Neonates are mostly indoors and hardly have any such contact.There are very few case reports reporting worm infestation in infants or neonates [2][3][4][5][6][7]. Enterobius vermicularis (E V) is a white slender nematode with a pointed tail.…”
mentioning
confidence: 99%